Policing and devolution in the UK: The ‘special’ case of Wales - Michael Harrison (Policing: A Journal of Policy and Practice, 2023)
Political devolution in the UK has been responsible for major legislative changes to police governance, policy, and practice. Although policing in Wales remains formally part of the unitary ‘England and Wales’ system, the devolution of other key policy areas have contributed to the emergence of a distinctive Welsh policy context. In this paper, we explore the ways in which the devolution settlement in Wales has, albeit inadvertently, resulted in growing divergence from policing in England. We argue that devolution has transformed the operation of policing in Wales and has added a significant degree of complexity for Welsh police forces. The paper raises several important questions for policing in post-devolution Wales and underlines the need for further empirical research that can explore the extent, causes and implications of divergence between the policing systems of the constituent nations of the United Kingdom.